2010
DOI: 10.1016/j.otohns.2010.06.791
|View full text |Cite
|
Sign up to set email alerts
|

Nasal and Exhaled Nitric Oxide in Allergic Rhinitis

Abstract: OBJECTIVE: 1) Establish current opinion from medico-legal sources based upon the following questions: Does the surgeon owe a duty of care to advise an x-ray for nasal fracture secondary to assault? Does a fracture demonstrated by x-ray result in the ability of the prosecution to establish a greater degree of harm against the victim? 2) Identify patients who underwent manipulation under anesthetic (MUA) of nasal fracture secondary to assault and investigate their legal outcomes. METHOD: A number of relevant med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 6 publications
2
19
0
1
Order By: Relevance
“…Some studies showed increased nasal NO levels in AR patients, whereas other studies demonstrated no differences, or even decreased nasal NO levels, in AR patients compared with control subjects . Moreover, nasal NO concentration was found to be significantly lower in a persistent allergic rhinitis group than in an intermittent group, even though exhaled NO concentration was significantly higher in the former group . One study demonstrated that nasal NO level was lower in patients with nasal polyps than in patients with asthma, allergic rhinitis, and control subjects .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed increased nasal NO levels in AR patients, whereas other studies demonstrated no differences, or even decreased nasal NO levels, in AR patients compared with control subjects . Moreover, nasal NO concentration was found to be significantly lower in a persistent allergic rhinitis group than in an intermittent group, even though exhaled NO concentration was significantly higher in the former group . One study demonstrated that nasal NO level was lower in patients with nasal polyps than in patients with asthma, allergic rhinitis, and control subjects .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise to asthma, a high expression of the NOS2 isoform has been reported in patients with AR . While FeNO is consistently high in AR, data on nNO are controversial as some studies found increased nNO levels, while others did not . These findings may be explained by the fact that high nNO concentrations derive from the induction of NOS in the inflamed mucosa provided osteomeatal patency .…”
Section: Introductionmentioning
confidence: 99%
“…Also, in the absence of asthma, allergic rhinitis patients had a higher level of exhaled NO than the normal control group. On the other hand, those with resistant allergic rhinitis had higher exhaled NO concentrations, while there was a lower concentration of nasal NO compared to the control group so that in the severe stages of the disease and rhinitis, which are resistant to NO treatment, nasal NO can be reduced (25). In 2014, Green et al studied the sensitivity of CRS patients and reported that a high percentage of patients with positive CRS had Positive Prick Test (SPT), and the highest sensitivity in these patients belonged to A. alternata, cat, and Ragweed (15).…”
Section: Discussionmentioning
confidence: 91%